ANALISIS PENGARUH PENGGUNAAN BAHAN BAKAR ALKOHOL TERHADAP PELEPASAN PANAS DAN KINERJA MESIN PEMBAKARAN - Wirawan, Tri Susilo (Jurusan Teknik Mesin Fakultas Sains dan Teknik Universitas Bangka Belitung, 2025)
Gasoline engines are crucial, especially in the transportation sector, and currently rely on fossil-based gasoline, which is expected to deplete. To meet domestic energy needs, the country must import gasoline. Therefore, there is a need for renewable energy sources that do not require major modifications to the engine. Methanol, a renewable alcohol fuel derived from plant materials, was tested in a 20% blend with gasoline in a TV-1 engine with a power output of 4.50 kW, a single cylinder, four-stroke configuration, and a cylinder volume of 661.45 cc. The research results indicate that the engine performance with the methanol blend is better in terms of cylinder pressure and heat release. The largest difference in cylinder pressure is 1.91 bar, while the largest difference in heat release is 1.64 J/°C. However, the specific fuel consumption for the methanol blend is higher compared to pure gasoline, with an average specific fuel consumption for the methanol-blended gasoline being 8.7% higher than that of pure gasoline.